(untitled) (Journal of Dhaka Medical College, 2023)
Background: Hypomagnesaemia has been associated with diminished respiratory muscle power, which maintains the work of breathing. However, the effect of magnesium on asthma has yet to be examined in our country. Therefore, assessing the serum magnesium level in acute severe asthma patients in a tertiary-level hospital was the study’s objective. Methods: The study was a hospital-based descriptive cross-sectional study conducted at the Department of Medicine and Department of Respiratory Medicine in DMCH. Each patient performed serum magnesium ion (Mg2+) during admission with other necessary investigations. Results: Fifty-seven percent of participants had hypomagnesemia, and 43% of patients had normal magnesium levels. Mean serum magnesium was 1.57±0.22 mg/dl [range: 1.25-2.23 ng/dl]. Although a higher proportion of patients with severe attacks (64.8%) had hypomagnesemia than those who had moderate-severity attacks (47.8%), the difference is not statistically significant (p >0.05). About 23% of patients stayed at the hospital for >3 days; among them, 73.9% had hypomagnesemia. Hypomagnesaemia patients had higher odds of staying at the hospital for >3 days, but the relation is not statistically significant (OR 2.62, 95% CI 0.93 -7.36, p >0.05). Conclusion: Hypomagnesaemia is present in half of the patients with acute severe bronchial asthma and is not associated with the severity of the disease and duration of hospital stay. J Dhaka Med Coll. 2022; 31(1) : 114-119